Computer Evidence: The Problem of its Reliability - Alfaro Valverde, Luis (2024)
The data contained in computer and technological devices are increasingly used as evidence in judicial processes, being decisive in the final decisions of judges. This is the so-called computer test. These are often valued uncritically as mere documentary evidence, without considering, among other things, their vulnerable and complex nature. Among the different problems that exist about this test, this study focuses specifically on those related to its reliability. Firstly, the aspects related to the nature of the computer test are examined, as well as its rational assessment. Then, the central question of its reliability is reviewed, related to the risk of its manipulation and its impact on it. Finally, some instruments are analyzed that allow their reliability to be adequately managed, such as expertise, the electronic signature and the intermediation of the notary in the certification of digital evidence.